LIQUIDITY MANAGEMENT OF COMMERCIAL BANKS: CURRENT APPROACHES AND IMPROVEMENT STRATEGIES - Abdusalamov Olimjon Eshmirzayevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The article analyzes contemporary liquidity management practices in commercial banks, examining regulatory requirements, balance-sheet structures, funding stability, and technological innovations that shape liquidity resilience. The study evaluates key indicators such as LCR, NSFR, LDR, cash-flow gap analysis, and stress testing, highlighting their role in mitigating short-term and long-term liquidity risks. It also identifies structural challenges faced by banks in emerging markets and proposes strategic directions for strengthening liquidity governance, improving forecasting accuracy, and integrating digital solutions into liquidity monitoring systems.